Animal models for neurodegenerative disease - Avila, Jesús; Lucas, José J.; Hernández, Félix (RSC drug discovery series, ISSN 2041-3203, 2011)
In recent years, medical developments have resulted in an increase in human life expectancy. Some developed countries now have a larger population of individuals aged over 64 than those under 14. One consequence of the ageing population is a higher incidence of certain neurodegenerative disorders. In order to prevent these, we need to learn more about them. This book provides up-to-date information on the use of transgenic mouse models in the study of neurodegenerative disorders such as Alzheimer's and Huntington's disease. By reproducing some of the pathological aspects of the diseases, these
Keywords: Nervous system : Degeneration; Nervous system : Degeneration : Animal models